The Role of Manipulating Photoperiod and Temperature in Oocyte Development of the Polychaete Hediste diversicolor (O.F. Müller, 1976) - Wang, Haiqing; Hagemann, Andreas; Malzahn, Arne M.; Handå, Aleksander; Uhre, Marianne; Kjørsvik, Elin; Reitan, Kjell Inge (Frontiers in Marine Science, 2020)
Three different experiments were conducted to examine the oocyte development of the polychaete Hediste diversicolor in response to changing daylength and temperature at three different periods of oogenesis. Worms collected during summer were reared under constant or decreasing daylengths and temperatures to test the synergistic effects of the summer–autumn daylength and temperature transition on oogenesis (Experiment I). Worms collected in late autumn were under mimicked or shortened seasonal changes in daylength to evaluate the effect of accelerated change on oocyte growth (Experiment II). Worms collected in spring were exposed to different temperature regimes to examine the effect of raising temperature on the synchronization of oocyte growth and maturation (Experiment III). Worms collected during summer showed the highest oocyte growth when exposed to constant temperatures combined with decreasing daylength and decreasing temperature combined with constant daylength. Worms collected in autumn showed 1.5 times higher oocyte growth rates when exposed to accelerated rate of change in daylength (2.5 times faster). Finally, worms collected in spring showed the highest oocyte maturation synchronicity when exposed to increased temperatures. We conclude that both daylength and temperature changes affect gametogenesis and oocyte maturation.